The relationship between Chinese preschool principal leadership styles and teacher leadership: Exploring the mediating effect of psychological capital - Zhang, Limin; Wu, Tingting; Liu, Lijia; Ren, Ping; Lin, Chaopai (Frontiers in Psychology, 2022)
Enhancing teacher leadership is not only one of the approaches to improving teaching and learning, but it is also essential to the success of education reform. Based on leader-member exchange theory, 294 preschool teachers in China were surveyed, and a structural equation model was established to explore the relationship between the participating teachers' principal leadership style, teacher leadership and psychological capital. The findings revealed a significant positive correlation between transformational and transactional leadership styles and preschool teacher leadership. The laissez-faire leadership style had no correlation with preschool teacher leadership. The transformational leadership style and transactional leadership style were significantly and positively correlated with psychological capital, while the laissez-faire leadership style was significantly and negatively correlated with psychological capital. The transformational leadership style can positively influence preschool teacher leadership directly and indirectly through psychological capital; and the transactional leadership style can only positively influence preschool teacher leadership indirectly through the mediating role of psychological capital. Preschool teachers' leadership can neither be directly influenced by a laissez-faire leadership style nor be indirectly influenced through the mediating role of psychological capital.